Incidencias De Las Estrategias De Promoción De Salud En El Control De Las Enfermedades Diarreicas En Niños Menores De 5 Años De Edad Que Acuden Al Dispensario Médico Buena Fé, Del Seguro Social Campesino, Cantón Buena Fé, Provincia De Los Ríos - Cabrera Casillas, Daniel Oswaldo (2015)
This investigation covered the main objective to analyze the impact of the strategies of health promotion in the control of diarrheal diseases in children 5 years of age attending the Medical Clinic of Rural Social Security, Canton Buena Fe, Los Rios Province , to know This research work was conducted at the Medical Clinic "good faith 1" Campesino Social Security, Canton Good Faith, located 14 km from the Panamerican Highway via Santo Domingo Quevedo. Los Rios province For tabulation of this research surveys with closed questions to health workers and mothers or parents Medical Clinic they were used; Additionally, a SWOT matrix was performed to establish the vulnerability and aprovechabilidad of surveys to determine the perception of them with the service provided by the medical clinic as well as their knowledge of hygiene and community participation. The results were that the staff working at the Medical Clinic has received inductions on diarrheal disease control training, but would improve the reduction of the disease if protocols previously established health shall apply also not a strategic plan applies health promotion designed exclusively for the control and prevention of diarrheal diseases; also they do not have the necessary number of professionals according to the charges required template. The main feature that helps reduce diarrheal disease is the integration of families.